1997
DOI: 10.1111/j.1540-8167.1997.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Properties of the Inferior Vena Cava‐Tricuspid Annular Isthmus in Patients with Typical Atrial Flutter

Abstract: Decremental conduction is not characteristic of activation through the isthmus when activation is assessed parallel and adjacent to the tricuspid annulus. Functional slowing or conduction delay does not develop in this region during typical atrial flutter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…[15][16][17] The surface ECG generally demonstrated negative flutter waves in leads II, III, and aVF, and isoelectric or positive flutter waves in lead V 1 . Clockwise type I atrial flutter was considered present if clockwise activation around the tricuspid annulus was demonstrated and concealed entrainment could be demonstrated from annular pacing sites within the tricuspid valve-eustachian ridge isthmus, with a postpacing interval similar to the flutter cycle length.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] The surface ECG generally demonstrated negative flutter waves in leads II, III, and aVF, and isoelectric or positive flutter waves in lead V 1 . Clockwise type I atrial flutter was considered present if clockwise activation around the tricuspid annulus was demonstrated and concealed entrainment could be demonstrated from annular pacing sites within the tricuspid valve-eustachian ridge isthmus, with a postpacing interval similar to the flutter cycle length.…”
Section: Definitionsmentioning
confidence: 99%
“…A deflectable quadripolar catheter (Cordis Webster, 2-5-2 mm spacing) was positioned at the inferolateral tricuspid annulus for pacing and recording from the lateral isthmus. 15 Annular activation during atrial flutter or atrial pacing was assessed by either a second roving deflectable quadripolar catheter, or a 20-electrode Halo catheter (Cordis Webster, 2-7-2 mm intervals). Patients were studied in the fasting state and sedated with intravenous midazolam and fentanyl.…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…An area of slow conduction has been shown to be present in the CTI, accounting for one-third to one-half of the AFL cycle length (CL) [8][9][10]. The CTI is anatomically bounded by the inferior vena cava and Eustachian ridge posteriorly and the tricuspid valve annulus anteriorly ( Figure 20.1a & b), both of which form lines of conduction block or barriers delineating a protected zone in the reentry circuit [5,[11][12][13].…”
Section: Pathophysiological Mechanisms Of Typical (And Reverse Typicamentioning
confidence: 99%
“…Comparison of CW and CCW AFL Tai et al (12) and Feld et al (11) demonstrated rate-dependent slowing of the trans-isthmus conduction, whereas Kinder et al (17) and Lin et al (7) did not show such a phenomenon using a similar pacing protocol. We think that these differences may depend on using different kinds of catheters (they may cause different positioning of the electrodes) and different calculating methods.…”
Section: Figure 1 Measurement Of the Conduction Velocity (Cv) In Isomentioning
confidence: 99%
“…We think that these differences may depend on using different kinds of catheters (they may cause different positioning of the electrodes) and different calculating methods. CCW and CW CVs of CTI seem to be also different in AFL patients compared with the control (11,17,18). Morita et al (19) has found that the CW conduction in the low RA isthmus was significantly slower than the CCW direction.…”
Section: Figure 1 Measurement Of the Conduction Velocity (Cv) In Isomentioning
confidence: 99%